Permeability functions for unsaturated soils - Leong, Eng Choon (2011)
This paper examines the three categories of permeability functions for unsaturated soils, including empirical, macroscopic, and statistical models. The theoretical backgrounds and performance of each category are examined against various experimental data. The paper also shows that it is possible to degenerate statistical models to macroscopic models and then to empirical models. A new empirical equation for the permeability function is suggested. The statistical model demonstrates good performance and can be readily applied. In some cases the performance of the statistical model can be further improved with the introduction of a correction factor.